Pelatihan Digital Marketing Pada Benih Cabe Unggul Untuk Meningkatkan Perekonomian Desa Siulak Tenang - Anggil Nopra Lova (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
This community service is carried out with the aim that chili farmers and BUMDes players in Siulak Tenang Village can understand and practice digital marketing for the chili seed products they produce and increase the income and economy of the people of Siulak Tenang Village. The chili seed digital marketing training was attended by 22 participants consisting of BUMDes officers and other members of the public who have an interest in digital marketing. The training was carried out by providing education and outreach about digital marketing, especially through the Shopee platform and Instagram social media which was then followed by exploration and digital marketing practices through shopee and Instagram. The output produced in this service is the formation of a BUMDes sub-business, namely chili peppers labeled ASCI. The trainees have professional Shopee and Instagram accounts and start filling out content for the promotion and sale of their BUMDes chili seed products.